Determination of Optimal Conditions for the Production of Laccase Enzyme by Local Isolate of Bacillus sp. - Nahil Shukur, Yassamin (Iraqi Journal of Science, 2023)
Fifty isolates of Bacillus sp. were subjected to the first and second screening to detect the ability to produce laccase enzyme and select the highest ones production of laccase on Petri plates containing nutrient agar supplemented with Cu2+.Syringaldazine was used as an indicator and substrate for the determination of laccase activity. Three isolates, which consumed less time to developed pink color were tested for the production of laccase quantitatively. The effective isolate B16 with significant amounts of laccase 1.84 unit /ml was selected for laccase study.The optimization studies revealed that the maximum laccase production was achieved when the production medium was at the following conditions: 5 days of incubation, temperature 35 C°, pH 7.0, copper sulphate 0.2 mM, galactose 3% as carbon source, 0.2% Tryptone as nitrogen source and K+ 1mM.